Determining the clog state of constructed wetlands using an embeddable Earth’s Field Nuclear Magnetic Resonance probe - Hill-Casey, Fraser; Hughes-Riley, Theodore; Bradley, C. R.; Newton, Michael Ian; Morris, Robert H. (Diffusion Fundamentals, 2014)
The recent rise in interest of green technologies has led to significant adoption of the constructed wetland as a waste water treatment technique. This increased popularity has only been mired by the decline in operational lifetime of wetland units, leading to the need for more regular, time consuming, and expensive rejuvenation techniques to be performed than initially anticipated. To extend operational lifetimes and increase efficiency of wetland units, it is crucial to have an accurate method to determine the internal state of the wetland system. The most important parameter to measure within the reed bed is the clog state of the system, which is representative of the overall system health. In previous work, magnetic resonance (MR) measurements, parameters of T1 and T2eff, have been demonstrated as extremely powerful tools to determine the internal clog state of a wetland [1, 2]. Measurements have been performed in a laboratory setting, using low field permanent magnet arrangements. This work presents an Earth’s Field Nuclear Magnetic Resonance (EFNMR) probe suitable for in situ measurements within constructed wetlands. We show T2eff and T1 measurements using the EFNMR probe. T1 values are shown to be sensitive to the change in the clog state with 1498 ms for the thickly clogged sample and 2728 ms for the thinly clogged sample. T2eff values are shown to be marginally more sensitive to clog state with 630 ms for a thickly clogged sample and 1212 ms for the thinly clogged sample. This gives distinguishable variation within both parameters suggesting that this probe is suitable for embedding into an operational constructed wetland. This work was conducted as part of an EU FP7 project to construct an Automated Reed Bed Installation, “ARBI”.